Suboptimal response rates to hypomethylating agent therapy in chronic myelomonocytic leukemia; a single institutional study of 121 patients. Issue 7 (3rd May 2019) - Coston, Tucker; Pophali, Prateek; Vallapureddy, Rangit; Lasho, Terra L.; Finke, Christy M.; Ketterling, Rhett P.; Carr, Ryan; Binder, Moritz; Mangaonkar, Abhishek A.; Gangat, Naseema; Al‐Kali, Aref; Litzow, Mark; et al.
Abstract: Hypomethylating agents (HMA) are currently the only FDA approved therapy for patients with chronic myelomonocytic leukemia (CMML). In the current retrospective study, we assessed response rates as adjudicated by the IWG (International Working Group) MDS (myelodysplastic syndrome) and MDS/MPN myeloproliferative neoplasm overlap syndrome response criteria, in 121 CMML patients treated with Azacitidine (AZA, n = 56) and Decitabine (DAC, n = 65). The overall response rates were 41% by the IWG MDS (AZA‐ 45%, DAC‐39%), and 56% by the IWG MDS/MPN (AZA‐56%, DAC‐58%) response criteria, with CR (complete remission) rates of <20% for both agents, by both criteria. There were no significant differences in response rates between proliferative and dysplastic CMML. Moreover, 29% of CMML patients in a CR with HMA progressed to AML (blast transformation), underscoring the limited impact of these agents on disease biology. Progression after HMA response was associated with a median overall‐survival (OS) of 8 months, while median OS in patients with primary HMA failure was 4 months. Lower serum LDH levels (<250 Units/L) were associated with HMA responses by both criteria; while ASXL1 and TET2 mutational status had no impact. HMA treated patients had a longer median OS (31 vs 18 months; P = .01), in comparison to those treated with conventional care regimens (excluding observation only patients), without any differences between AZA vs DAC ( P = .37). In conclusion, this study highlights the inadequacies of HMA therapy in CMML, retrospectively validates the IWG MDS/MPN response criteria and underscores the need for newer, rationally derived therapies.